EXPLORING THE IMPACT OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE: A STUDY OF PERSON-JOB FIT AT THE MALANG REGENCY EDUCATION OFFICE - Amalia Chairini; Siwi Dyah Ratnasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the impact of person-job fit on employee performance with work motivation as a mediator in the Malang Regency Education Office. The research method is quantitative, involving 65 respondents. Data was collected using questionnaires and analyzed with SmartPLS version 4.0 software. The data analysis results indicate that person-job fit significantly influences work motivation, work motivation significantly impacts employee performance, but person-job fit itself does not have a significant direct effect on employee performance. The mediation analysis shows that work motivation plays a significant role in mediating the relationship between person-job fit and employee performance. Based on the findings, the implications of this study are that the management of the Malang Regency Education Office needs to pay attention not only to the aspect of placing employees according to their competencies, but also to strategies for increasing work motivation as a strengthening factor. Efforts such as giving awards, opportunities for self-development, continuous training, and creating a supportive work environment will strengthen the effect of person-job fit on performance through increased motivation